2018
DOI: 10.1007/s10565-018-9435-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel and effective inhibitor combination involving bortezomib and OTSSP167 for breast cancer cells in light of label-free proteomic analysis

Abstract: Altogether, the results presented here indicate that bortezomib + OTSSP167 is a novel and effective combination and may be tested further for cancer treatment in vivo and in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Currently, a small number of UPS-targeting drugs (e.g., bortezomib) are available. These drugs, which are selective proteasome inhibitors, are very effective in treating refractory melanoma and mantle cell lymphoma [26]. These findings together with our results indicate that UBB might both serve as a new therapeutic target and assist in the diagnosis of and prognosis predictions in ovarian carcinoma.…”
Section: Discussionsupporting
confidence: 58%
“…Currently, a small number of UPS-targeting drugs (e.g., bortezomib) are available. These drugs, which are selective proteasome inhibitors, are very effective in treating refractory melanoma and mantle cell lymphoma [26]. These findings together with our results indicate that UBB might both serve as a new therapeutic target and assist in the diagnosis of and prognosis predictions in ovarian carcinoma.…”
Section: Discussionsupporting
confidence: 58%
“…The data were analyzed and graphed with GraphPad Prism 5 program. The IC 50 values of bortezomib were then obtained by using nonlinear regression to fit the data to the log(inhibitor) versus response-variable slope (Okur and Yerlikaya 2019).…”
Section: Cell Maintenance and Development Of Resistant Cellsmentioning
confidence: 99%
“…For instance, Chen and Madura showed that the proteasomal subunits, as well as the activity of the proteasome, were increased by 2-32 fold in more than 90% of primary breast cancer cells as compared to the benign solid tumors (Chen and Madura 2005). Furthermore, numerous studies showed that proteasome inhibitor bortezomib alone has significant growth suppressing and apoptotic activity in many cancer cell lines as well as encouraging antitumor activity in combination with other cytotoxic agents (Adams 2002;Escobar et al 2011;Okur and Yerlikaya 2019;Yerlikaya and Erin 2008). In fact, the 26S proteasome inhibitor bortezomib and carfilzomib are approved by the Food and Drug Administration (FDA) in 2003 and 2012, respectively, for the treatment of patients with relapsed and refractory multiple myeloma (MM) (Kane et al 2003;Thompson 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the anti-lymphoma activity of OTSSP167, in vitro combination studies were performed. Previously, studies in multiple myeloma and breast cancer demonstrated that combining OTSSP167 with standard-ofcare agents (including lenalidomide, pomalidomide, and bortezomib) could increase the anti-cancer effect of the standard-of-care agent 18,53 . A promising novel agent in clinical development in DLBCL and MCL is the selective Bcl-2 inhibitor venetoclax (also known as ABT-199).…”
Section: Discussionmentioning
confidence: 99%